2008
DOI: 10.1002/ptr.2388
|View full text |Cite
|
Sign up to set email alerts
|

Improved cognitive performance after dietary supplementation with a Pinus radiata bark extract Formulation

Abstract: Dietary interventions may have the potential to counter age-related cognitive decline. Studies have demonstrated an improvement in age-related cognitive impairment in animals after supplementation with plant extracts containing flavonoids but there are few human studies. This double-blind, controlled study examined the effects on cognitive performance of a 5 week supplementation with Enzogenol Pinus radiata bark extract containing flavonoids, in 42 males aged 50-65 years, with a body mass index >25. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 28 publications
2
68
1
Order By: Relevance
“…The most robust cognitive benefits were specific to the domain of working memory, providing support to the predictions of other researchers that measures of fluid intelligence may be responsive to treatment with vitamin formulations due to the role of these nutrients in the maintenance of CNS function and production of neurotransmitters relevant to memory function (Cockle et al 2000;Bryan et al 2002;Haskell et al 2008). Working memory represents an important component of fluid intelligence and growing evidence indicates that working memory may represent a cognitive domain which benefits preferentially from nutraceutical intervention (Pipingas et al 2008;Ryan et al 2008;MacReady et al 2011). Performance on the same spatial working memory task included in the current study has demonstrated improvements following 5 weeks supplementation with a flavonoid blend (Pipingas et al 2008), indicating that this measure is sensitive to both multivitamin and flavonoid intervention.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The most robust cognitive benefits were specific to the domain of working memory, providing support to the predictions of other researchers that measures of fluid intelligence may be responsive to treatment with vitamin formulations due to the role of these nutrients in the maintenance of CNS function and production of neurotransmitters relevant to memory function (Cockle et al 2000;Bryan et al 2002;Haskell et al 2008). Working memory represents an important component of fluid intelligence and growing evidence indicates that working memory may represent a cognitive domain which benefits preferentially from nutraceutical intervention (Pipingas et al 2008;Ryan et al 2008;MacReady et al 2011). Performance on the same spatial working memory task included in the current study has demonstrated improvements following 5 weeks supplementation with a flavonoid blend (Pipingas et al 2008), indicating that this measure is sensitive to both multivitamin and flavonoid intervention.…”
Section: Discussionsupporting
confidence: 58%
“…Working memory represents an important component of fluid intelligence and growing evidence indicates that working memory may represent a cognitive domain which benefits preferentially from nutraceutical intervention (Pipingas et al 2008;Ryan et al 2008;MacReady et al 2011). Performance on the same spatial working memory task included in the current study has demonstrated improvements following 5 weeks supplementation with a flavonoid blend (Pipingas et al 2008), indicating that this measure is sensitive to both multivitamin and flavonoid intervention.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Enzogenol displays a positive influence on cognitive performance, specifically on working memory, a type of short-term memory. In combination with vitamin C, Enzogenol improved the response speed of spatial working memory and immediate recognition tasks (Pipingas et al, 2008). In patients with 3-12 months post-mild traumatic brain injury, self-perceived cognitive failures were reduced (Theadom et al, 2013).…”
Section: Neuroprotective Effectsmentioning
confidence: 99%